(untitled) (International journal of medical sciences, 2026)
Mechanical ventilation (MV) is one of the fundamental methods of intensive care in newborns with severe respiratory failure. Over recent decades, advances in respiratory technologies, the introduction of surfactant therapy, and the development of non-invasive ventilation techniques have led to a significant reduction in neonatal mortality, including improved survival of infants with extremely low birth weight. At the same time, the use of MV remains associated with the development of a wide range of complications caused by the immaturity of lung tissue, the impact of mechanical and biochemical factors, and the systemic inflammatory response. The most clinically significant complications include ventilator-induced lung injury, bronchopulmonary dysplasia, hemodynamic disturbances, central nervous system damage, and infectious complications. The aim of this review is to provide a systematic and critical analysis of the contemporary scientific literature on complications of mechanical ventilation in newborns, with a focus on pathophysiological mechanisms, risk factors, clinical relevance, and preventive approaches. The presented data highlight the necessity of individualized respiratory support and the further development of lung-protective ventilation strategies in neonatal intensive care.